Performance of Sustainable PE-ECC and PVA-ECC Using Dune Sands and GGBS Under Elevated Temperatures - Shahin, Eyad (2024)
A Master of Science thesis in Civil Engineering by Eyad Shahin entitled, “Performance of Sustainable PE-ECC and PVA-ECC Using Dune Sands and GGBS Under Elevated Temperatures”, submitted in August 2024. Thesis advisor is Dr. Jamal Abdalla and thesis co-advisor is Dr. Rami Haweeleh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).